Factors influencing micro and small enterprise's decision to innovate in Kenya - Peter Njiraini; Paul Gachanja; Jacob Omolo (Journal of Global Entrepreneurship Research, 2018)
An enterprise's propensity to innovate has been recognised to have an important bearing on its performance. In Kenya empirical work on micro and small enterprises (MSEs) propensity to innovate is still nascent in spite of the pivotal role played by these enterprises in the economy. The current paper used a Probit econometric model to analyse factors that influence MSE's decision to innovate or not. Results from the analysis show that the average number of years of education for a production worker, physical capital intensity, age of an MSE, access to finance and size of an MSE are important factors influencing MSEs innovation decisions. Higher foreign ownership and manager's experience were found to act as hindrances towards MSEs' decision to innovate. Based on the study findings it is clear that human capital skills and an MSE's resource endowment positively influences MSEs innovativeness.From a theoretical perspective, there is need for skills segmentation to isolate human capital skills that are most relevant for stimulating MSEs innovative activities. Firm level and policy level strategies are also needed to improve the technical skills of the average MSEs' production workers across the country. Subsidisation of physical capital and financial services for MSEs should also be used to promote these enterprises innovativeness.
Keywords: 650; Micro and small Enterprise; Innovation; Propensity